Capital social, santé et minorités francophones - Bouchard, Louise; Gilbert, Anne; Landry, Rodrigue; Deveau, Kenneth (Revue canadienne de santé publique / Canadian Journal of Public Health, 2006)

Social capital, health and Francophone minorities - Bouchard, Louise; Gilbert, Anne; Landry, Rodrigue; Deveau, Kenneth (Canadian Journal of Public Health / Revue canadienne de santé publique, 2006)
The goal of this article is to outline the analytical perspectives of the concept of social capital regarding health and health management. Social capital, as defined in terms of social networks and resources, has a positive impact on a number of areas, notably the health, well-being, and social and economic development of communities. It is also a useful tool for implementing social policy, especially for marginal populations, the elderly, social assistance payments, etc. An action strategy based on the support and development of networks is the key to achieving the social development, health, and well-being of populations. The social ties promoted by these networks provide people with social, cognitive, and emotional support. This has a direct impact on their self-esteem and sense of personal achievement. They also facilitate access to social resources, including social advancement opportunities. In this paper, we examine the vitality, determinants of health, and health management of Canada’s minority Francophone communities.

Évaluation de l’offre active des services de santé de première ligne - Comité santé en français de Fredericton (Groupe Progecom communication et stratégies d’entreprise, 2006)

Étude sur les besoins en formation clinique et en formation continue des professionnels de la santé des communautés francophones en situation minoritaire - Consortium national de formation en santé (2006)

Les services de santé au Canada : une perspective linguistique - Lacroix, Frédéric (L'Action nationale, 2006)

Accès aux services de santé et aux services sociaux en anglais au Québec. Rapport de données de base 2005-2006 - Pocock, Joanne (Réseau communautaire de santé et de services sociaux, 2006)

Préparer le terrain. Soins de santé primaires en français dans le Sud de l'Ontario. Rapport régional - Réseau franco-santé du Sud de l'Ontario (2006)

Préparer le terrain : soins de santé primaires en français en Ontario. Rapport provincial - Réseau francophone de santé du Nord de l’Ontario; Réseau de santé en français du Moyen-Nord de l’Ontario; Réseau franco-santé du Sud de l’Ontario; Réseau des services de santé en français de l’Est de l’Ontario (2006)

Des services de santé en français dans un Nord en mutation. Un défi intercommunautaire - Réseau Santé en français au Nunavut (Association des Francophones du Nunavut, Santé en français au Nunavut, 2006)

The network’s approaches for the maintenance and creation of primary health services in English for the Quebec City region - Sanderson, Duncan; Grégoire, Louise; Reinharz, Daniel (Agence de la santé et des services sociaux de la Capitale-Nationale & Direction régionale de santé publique, 2006)
fs-ref-orig: Sanderson, D., Grégoire, L., & Reinharz, D. (2006). The network’s approaches for the maintenance and creation of primary health services in English for the Quebec City region. Agence de la santé et des services sociaux de la Capitale-Nationale & Direction régionale de santé publique. fs-code-orig: Sanderson-2006